If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 19 = 43 + -7x Reorder the terms: 19 + 5x = 43 + -7x Solving 19 + 5x = 43 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 19 + 5x + 7x = 43 + -7x + 7x Combine like terms: 5x + 7x = 12x 19 + 12x = 43 + -7x + 7x Combine like terms: -7x + 7x = 0 19 + 12x = 43 + 0 19 + 12x = 43 Add '-19' to each side of the equation. 19 + -19 + 12x = 43 + -19 Combine like terms: 19 + -19 = 0 0 + 12x = 43 + -19 12x = 43 + -19 Combine like terms: 43 + -19 = 24 12x = 24 Divide each side by '12'. x = 2 Simplifying x = 2
| 0=x+(4+3x)7 | | 8x-14+6x-2=180 | | 8x-14+6x-2= | | -10+x+x+4-5=7x-5 | | 3x+8y=23forx | | 4/1=11/c | | -9(5a-8)+(9q-6)= | | 4m-29=-28+3m | | 0=4+(8x+9)2 | | X^2+27x+169= | | 7s-7=-47+2s | | x^4+x^2-90= | | 40(x-20)=20(6) | | 7(1-8x)=7+2x | | 3x^5+3x^4-15x^3+6x^2=0 | | x-1/15=2/15 | | 0=x+5(5x+1) | | (y-2)(y+1)= | | x^6-90= | | x−1/15=2/15 | | 3=x3/3 | | 3=x/3/3 | | X^2+25x+141= | | x-1/10=615 | | 0=7(2+x)+6x | | x-1/24=5/24 | | 8x-7=x-7 | | 13(x-52)=56 | | 12/X=14/7/2 | | 0.76=-(log)x | | 2/5×-1/3×=3 | | 9(x+3)=4(3+x) |